Sistem Informasi Geografis (SIG) Pemetaan Lokasi Pertambangan Batu Bara Berbasis Quantum GIS (Studi Kasus: PT. Hasil Bumi Kalimantan) - Fenando, Fenando (Asosiasi Doktor Sistem Informasi Indonesia, 2021)
During this time, the determination of the mine coordinates location done by the fieldman of PT. Kalimantan Earth Results was using a GPS locator. Found 27 points of coal mines and 18 coal ports spread across the southern Sumatra region. At present the process of recording and mapping locations is still done conventionally, causing frequent data loss, inaccuracies in the location of mining and information about mining results are less up-to-date. Systematic determination of location points is needed to make the companies and customers easier to see the coal mine profiles, coal quality, find out the location of each mine, and up-to-date mining results reports via webgis The prototype model was chosen as a method in system development. As well as UML (Unified Modeling Language), Quantum GIS (Qgis) and php will be used for the designers, builders of the webgis. This research is expected to produce a geographic information system (GIS) mapping of coal mining location points.